Respuesta :

Answer:

The answer to your question is:            y = -1/6 x + 1/2

Step-by-step explanation:

Data

A (-3, 1)

B (3, 0)

Formula

               m = (y2 - y1) / (x2 - x1)

               y = mx + b

               (y - y1) = m(x - x1)

Process

              m = (0 - 1) / (3 + 3)

              m = -1 / 6

             ( y - 1) = -1/6 (x + 3)

              6 ( y - 1) = -1(x + 3)

              6y - 6 = -x - 3

              6y = - x - 3 + 6

              6y = -x + 3

              y = -1/6 x + 3/6

              y = -1/6 x + 1/2

              x + 6y -3 = 0

              x = -6y + 3

ACCESS MORE